Effect of surgical approach on erectile function recovery following bilateral nerve‐sparing radical prostatectomy: an evaluation utilising data from a randomised, double‐blind, double‐dummy multicentre trial of tadalafil vs placebo. (20th April 2015) - Stolzenburg, Jens‐Uwe; Graefen, Markus; Kriegel, Christian; Michl, Uwe; Martin Morales, Antonio; Pommerville, Peter J.; Manning, Martina; Büttner, Hartwig; Henneges, Carsten; Schostak, Martin
<x xml:space="preserve">Abstract</x> Objectives To report pre‐specified and exploratory results on the effect of different surgical approaches on erectile function (EF) after nerve‐sparing radical prostatectomy (nsRP) obtained from the multicentre, randomised, double‐blind, double‐dummy REACTT trial of tadalafil (once a day [OaD] or on‐demand [pro‐re‐nata, PRN]) vs placebo. Patients and Methods Patients aged <68 years with normal preoperative EF who underwent nsRP for localised prostate cancer (Gleason ≤7, prostate‐specific antigen [PSA] <10 ng/mL) were randomised after nsRP 1:1:1 to 9‐month double‐blind treatment with tadalafil 5 mg OaD, tadalafil 20 mg PRN, or placebo, followed by 6‐week drug‐free washout, and 3‐month open‐label OaD treatment (all patients). Recovery of EF was defined as an International Index of Erectile Function (IIEF)‐EF domain score of ≥22 and normal orgasmic function was defined based on IIEF Question 10. Both parameters were analysed at the end of washout using logistic regression including terms for treatment, country, visit, visit‐by‐treatment interaction, age group, nerve‐sparing score (perfect = 2, non‐perfect >2), and surgical approach (open surgery, robot‐assisted laparoscopy, conventional laparoscopy, other). Time to EF recovery was analysed post hoc with a Cox proportional‐hazards model including terms for treatment, age‐group, country, surgical approach and surgery‐by‐treatment interaction. Results Of 422 patients treated, 189 underwent open surgery, 115 robot‐assisted laparoscopy, 88 conventional laparoscopy and 30 surgery classified as 'other'. The odds of achieving EF recovery at the end of drug‐free washout were about twice as high for the robot‐assisted laparoscopy group compared with the open surgery group (odds ratio 2.42; 95% confidence interval [CI] 1.24, 4.72; P = 0.029). Patients who underwent robot‐assisted laparoscopy were significantly more likely to recover during double‐blind treatment compared with patients who underwent open surgery (hazard ratio 1.92; 95% CI 1.17, 3.15; P = 0.010). No favourable effect of conventional laparoscopy compared with open surgery could be seen. Conclusion These results may provide further insights into the role of surgery on EF recovery after nsRP. However, the trial was not designed for these analyses and further prospective studies are needed.